Hydrodynamic and Microscopic Investigations of Polysaccharides and Glycopeptide Antibiotics of Ophthalmological Importance - Chun, Taewoo (2023)
The thesis consists of two main themes: the eye-drop study for dry eye syndrome and the antibiotic study for antibiotic resistance. Hyaluronic acid (HA) has been commonly used in eyedrop formulations. A difficulty has been its short residence time on ocular surfaces due to ocular clearance mechanisms which remove the polysaccharide almost immediately. To prolong its retention time, tamarind seed gum polysaccharide (TSP) is mixed as a helper biopolymer with HA. Here I look at the hydrodynamic characteristics of HA and TSP (weight average molar mass Mw and viscosity [η]) and then explore the compatibility of these polymers, including the possibility of potentially harmful aggregation effects. The research is based on a novel combination of three methods: sedimentation velocity in the analytical ultracentrifuge (SV-AUC), size-exclusion chromatography coupled to multiangle light scattering (SEC-MALS) and capillary viscometry. For the mixed HA-TSP systems, SEC-MALS indicates the possibility of a weak interaction. However, further investigation using sedimentation coefficient (s) distributions obtained from SV-AUC measurements together with intrinsic viscosity demonstrated no evidence of any significant aggregation phenomenon, reassuring in terms of eye-drop formulation technology involving these substances. The other topic is about the natural glycopeptide antibiotic teicoplanin used for the treatment of serious Gram-positive related bacterial infections and it can be administered intravenously, intramuscularly, topically (ocular infections), or orally. The hydrodynamic properties of teicoplanin A2 (M1 = 1879.7 g/mol) were examined in phosphate chloride buffer using sedimentation velocity and sedimentation equilibrium in an analytical ultracentrifuge together with capillary (rolling ball) viscometry. In the concentration range, 0-10 mg/mL teicoplanin A2 was found to self-associate plateauing > 1 mg/mL to give a molar mass of (35400 ± 1000) g/mol corresponding to ~ (19 ± 1) mers, with a sedimentation coefficient s20, w = ~ 4.65 S. Methicillin-resistant Staphylococcus aureus (MRSA) and enterococci have managed to avoid the antimicrobial activity of glycan antibiotics. Aggregations of antibiotics with mucins lead to long exposure and selection pressure to push forward further increases in resistant species in microbes. This study was focused on any potential interactions of teicoplanin with bovine submaxillary mucin (BSM) as an ocular mucin model, based on the relatively novel combination of hydrodynamic and microscopic techniques: SV-AUC, dynamic light scattering (DLS), and environmental scanning electron microscopy (ESEM). For the mixture of teicoplanin with the lowest concentration (0.125 mg/mL) and BSM, SV-AUC showed no interactions, while for higher concentrations (1.25 mg/mL and 12.5 mg/mL), teicoplanin was shown to have weak interactions with BSM and aggregates in the distributions of both sedimentation coefficients by SV-AUC and hydrodynamic radii by DLS.